Enhanced Spin Current in Ni81Fe19/Cu–CuOx Bilayer with Top and Sideways Oxidization. Issue 14 (25th February 2023) - An, Taiyu; Cui, Bin; Liu, Liang; Zhang, Mingfang; Liu, Fufu; Liu, Weikang; Xie, Jihao; Ren, Xue; Chu, Ruiyue; Cheng, Bin; Jiang, Changjun; Hu, Jifan
Abstract: Generation and manipulation of spin current are the cores of spintronic devices, which are intensely pursued. Heavy metals with strong spin–orbit coupling are commonly used for the generation of spin current, but are incompatible with the mass production of devices, and the polarization of spin current is limited to be in‐plane. Here, it is shown that the spin current with strong out‐of‐plane polarization component can be generated and transmitted in Ni81 Fe19 /Cu–CuO x bilayer with sideways and top oxidizations. The charge‐to‐spin current conversion efficiency can be enhanced through the spin currents consisting of both out‐of‐plane polarization ( σz ) and in‐plane polarization ( σy ) induced by spin‐vorticity coupling. Such a spin current is demonstrated to be closely related to the lateral oxidization gradient and can be controlled by changing the temperatures and times of annealing. The finding here provides a novel degree of freedom to produce and control the spin current in spintronic devices. Abstract : A sizeable spin current with strong out‐of‐plane polarization component can be generated and transmitted in Ni81 Fe19 /Cu–CuO x bilayer with sideways and top oxidizations based on the spin‐vorticity coupling. The charge‐to‐spin current conversion can be manipulated by changing the annealing temperature, time, and the Hall‐bar channel width, providing a novel approach to developing efficient spintronic devices.